Penerapan Trainer Human Machine Interface (HMI) Berbasis CX-Designer Sebagai Media Pembelajaran Programmable Logic Controller (PLC) - Angga Septian MN (Teknik Informatika Universitas Pamulang, 2018)
The purpose of this research is to create a learning media design in the Programmable Logic Controller (PLC) lecture in the form of CX-Designer-based Human Machine Interface (HMI) trainer integrated with CX-Programmer. The appropriate HMI design will make the program trial work easier and more efficient. The effectiveness of HMI as a learning media provides the information needed, so that the planning can run with maximum efficiency. The research method used is an experimental method with a design to make a product in the form of a trainer to test a program that has been designed by the operator. The results of this study can be concluded that the use of CX-Designer-based HMI trainers can be used in understanding the logic circuit of a program very easily and quickly in practicing programming skills in the PLC.